Bullying or a Means to an End?. Issue 4 (4th May 2019) - Mitchell, Murray
Abstract : There may sometimes be a thin line of distinction among bullying, paternalism, parenting and teaching, with intent being a key factor. Is the action taken for the good of the recipient or simply because the authority figure has power? This Viewpoint calls for personal reflection on the behaviors of teachers and teacher educators toward their students.